Pendidikan Gizi Seimbang bagi Ibu-Ibu yang Memiliki Anak Usia 3-5 Tahun di Desa Kopen Boyolali - Setyaningrum Rahmawaty; Dyah Intan Permatasari; Beni Setiono; Wido Setiawan (Warta LPM, 2022)
Low level of mothers’ knowledge on food and nutritional status has been reported to contribute the high prevalence of malnutrition of children aged 3-5 years in Kopen Village, District Teras Boyolali. The aim of this community service was to educate mothers about a balanced nutrition. Twenty-four mothers who have children aged 3-5 years were participated in this program. Each mother followed a half day nutritional education presented in 2 sections which were interactive discussion using power point and cooking demonstration. Before and after jointed the class, each mother completed a questionnaire consisted of 12 items questions about nutritional status and a balanced nutrition. The average (minimum, maximum) knowledge score before and after the program were 8.4 (5.0, 11.0) and 9.5 (7.0, 11.0) respectively. Of all participants, 70.8% showed an increase in their knowledge score following the program. The highest improvement of mothers’ knowledge score was on the statement ‘Children aged 1-3 year is a passive consumer, while 4-5 year is an active consumer’, followed by ‘Mother should not push children for eating when they are tired after playing’. While the lowest mothers’ knowledge score was on the statement ‘Fruits are not suitable for children because can cause diarrhoea’ followed by ‘Children who consume egg can suffered from allergy’ and ‘Meal cooking technique for children under 5 years is to cook the food until soft’.